SHM_3265129_3D Vendel Fragment - Serpent Head Helmet Fitting - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a helmet fitting fragment from Vendel Boat Grave 10 in Vendel, Uppsala. The fragment, which would have sat between the eyebrows, depicts a stylized serpent head and is dated to the eponymous Vendel Period. It is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collections platform

https://dyncoll.ht.lu.se/artifact_view.php?item=977

Link to Sök I Samlingarna

https://samlingar.shm.se/object/ab807fe8-b254-4e30-9f45-ec4fec544a5c
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Vendel Period; Dynamic Collections; 3D Model; Museum Object; Vendel; Photogrammetry; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi